KELUARGA HAMBA TUHAN (STUDI PATRIOLOGI DAN PENERAPANNYA BAGI PELAYAN TUHAN MASA KINI MENURUT 1 TIMOTIUS 3:5) - Sihombing, Bernike (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
The family of a servant of God can be a model practice in ministry, through the experiences he has had, it can be a lesson to know firsthand how family life is. And through the life of a servant of God with his family, he can indirectly provide an example to those around him of what a good and harmonious family life of a servant of God is like and one that is pleasing to God. This topic will be discussed and refers to 1 Timothy 3:5 such as First, explaining what are the qualifications of the life of a servant of God and his family. Second, explaining how the character of a servant of God in fostering his family both in his daily life and in relation to carrying out his duties as a servant of God, Third, explaining how his temperament and soul behave when carrying out his duties as a servant of God.